Optically Modulatable Blue Fluorescent Proteins - Jablonski, Amy E. (2013)
Blue fluorescent proteins (BFPs) offer visualization of protein location and behavior, but often suffer from high autofluorescent background and poor signal discrimination. Through dual-laser excitation of bright and photoinduced dark states, mutations to the residues surrounding the BFP chromophore enable long-wavelength optical modulation of BFP emission. Such dark state engineering enables violet-excited blue emission to be increased upon lower energy, green co-illumination. Turning this green co-illumination on and off at a specific frequency dynamically modulates collected blue fluorescence without generating additional background. Interpreted as transient photoconversion between neutral cis- and anionic trans- chromophoric forms, mutations tune photoisomerization and ground state tautomerizations to enable long-wavelength depopulation of the millisecond-lived, spectrally shifted dark states. Single mutations to the tyrosine-based blue fluorescent protein T203V/S205V exhibit enhanced modulation depth and varied frequency. Importantly, analogous single point mutations in the non-modulatable BFP, mKalama1, creates a modulatable variant. Building modulatable BFPs offers opportunities for improved BFP signal discrimination vs. background, greatly enhancing their utility.